MYCOLOGICAL ANALYSIS AND AFLATOXIN B1CONTAMINANT ESTIMATION OF HERBAL DRUG RAW MATERIALS - Rajeshwari, Puttaswamy; Raveesha, KoteshwarAnandrao (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The present study explores the fungal contamination of important herbal drug raw materials (HDRM), which are widely used in the preparation of many herbal drugs. Understanding of the microbial contamination status of HDRM is one of the important steps to ensure the safety and efficacy of herbal drugs. Materials and Methods: Eighteen samples of six herbal drug raw materials (HDRM) viz., Acorus calamus Linn., Cassia angustifolia Vahl., Centella asiatica (Linn.) Urban, Myristica fragrans Houtt.,Tinospora cardifolia (Wild) Miers and Withania somnifera (Linn.) Dunal, were screened for fungal contamination, by employing serial dilution method. All the isolates of Aspergillus flavus were screened for their ability to produce aflatoxin B1 (AB1) and highly contaminated samples were subjected to AB1 estimation by using Thin Layer Chromatography (TLC), spectrophotometric method and occurrence of Aflatoxin B1 was confirmed by Liquid Chromatography-Mass Spectrometry analysis (LCMS). Results: A total of 302 isolates of 42 fungal species belonging to 17 genera were found in association with test the samples. More than 61% of A. flavus isolates tested positive for production of AB1 and highest yield recorded was 5008.20 ppb from the isolates of T. cordifolia. Amongthesix highly contaminated samples three samples tested positive for AB1. Highest AB1 was recorded from T. cordifolia (104.19 µg/kg), followed by A. calamus (13.73 µg/kg) and M. fragrans (12.02 µg/kg). Conclusion: Assessment of fungal and mycotoxin contamination should be a part of the quality check while selecting HDRM for manufacture of herbal products. Safeprocessing and storage practices are necessary.